DEVELOPMENT OF LEARNING MEDIA BASED ON AUGMENTED REALITY ON MATERIALS OF CHANGING CONDITIONS OF THE EARTH - Safrina Junita Rina (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Technology-based learning media is an innovation in the current learning process. The aim of this research is to produce the development of augmented reality-based media in Phase C science learning, especially regarding changes in earth conditions. The media must meet valid criteria, be very practical and effective. The method used in this development is Research and Development (R&D) with the ADDIE development model which consists of the following steps: Analysis, Design, Development, Implementation, Evaluations. The data collection techniques are used validation of media, materials, language, teacher response questionnaires and test questions. The data analysis technique uses quantitative descriptive analysis. The results of the research show that the development of augmented reality-based learning media on material on changes in earth conditions which was developed based on material validators, media validators, language validators to analyze the level of validity obtained a score of 92.86% with very valid criteria, the teacher response questionnaire validator for the field of practicality got a score 92.5% with very practical criteria and the evaluation question validator which aims to see the level of effectiveness obtained a score of 80.7% with effective criteria. So the development of augmented reality-based learning media in Phase C science and science learning on changes in earth conditions is very valid, very practical and effectively used as a medium in the learning process.